A case of Haemophilus parainfluenzaepneumonia. Issue 7 (1st July 2000) - Pillai, A; Mitchell, J L; Hill, S L; Stockley, R A
Abstract : A 41 year old woman presented with community acquired pneumonia (CAP) which failed to resolve following treatment with amoxycillin and cefaclor prior to referral. Quantitative culture of sputum revealed a pure growth of Haemophilus parainfluenzae and, following antibiotic susceptibility testing of the isolate, ciprofloxacin was prescribed resulting in resolution of the infection. Immunological investigations showed that the patient had a high titre of H parainfluenzae specific IgM. The combination of a pure growth of H parainfluenzae, a response to appropriate antimicrobial therapy, and the presence of a specific antibody response indicated that this organism had a pathogenic role in the patient's pneumonia and should be considered in the differential diagnosis of CAP.